The Effect of Self-Regulation and Peer Attachment on Adversity Quotient in Quran Reciter Students - Siti Hapidoh; Baidi Bukhori; Lucky Ade Sessiani (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2019)
Adversity quotient play an important role in the life of every student of Islamic boarding school, especially Quran reciter student. The life of the boarding school with strict regulations and a busy schedule of activities requires students to have a high adversity quotient. Only students who have the ability to control themselves and good interpersonal relationships can survive in the boarding school. This study aimed to test the effect of self-regulation and peer attachment on the adversity quotient of Quran reciter students. There were 127 students of Islamic boarding school situated in Ngaliyan Sub-district, Semarang City, involved as the samples, which were collected using sampling quota technique. The data were collected using self-regulation scale, peer attachment scale, and adversity quotient scale, and were analyzed using multiple regression technique. The result of the analysis showed that self-regulation and peer attachment have simultaneous and partial effects on adversity quotient. Simultaneously the two independent variables affect the adversity quotient by 40.9%, while partially self regulation can affect the adversity quotient greater, that is by 62.1%, and peer attachment affects by 12.8%. Activities that are oriented towards increasing self-regulation of students and increasing peer-attachment among students become important implications of the results of research.